2007
DOI: 10.1038/sj.ki.5002077
|View full text |Cite
|
Sign up to set email alerts
|

Association of intradialytic blood pressure changes with hospitalization and mortality rates in prevalent ESRD patients

Abstract: The relationship between blood pressure (BP) and clinical outcomes among hemodialysis patients is complex and incompletely understood. This study sought to assess the relationship between blood pressure changes with hemodialysis and clinical outcomes during a 6-month period. This study is a secondary analysis of the Crit-Line Intradialytic Monitoring Benefit Study, a randomized trial of 443 hemodialysis subjects, designed to determine whether blood volume monitoring reduced hospitalization. Logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
189
5
12

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(218 citation statements)
references
References 32 publications
(46 reference statements)
12
189
5
12
Order By: Relevance
“…However, we note that hemodynamic factors were still important to these longer-term models. Previous work has shown BP variability to be an important correlate of cardiovascular outcomes (28)(29)(30). Overall, these results suggest that the EHR data are not only suitable for near-term prediction but in fact, optimal for it.…”
Section: Discussionsupporting
confidence: 50%
“…However, we note that hemodynamic factors were still important to these longer-term models. Previous work has shown BP variability to be an important correlate of cardiovascular outcomes (28)(29)(30). Overall, these results suggest that the EHR data are not only suitable for near-term prediction but in fact, optimal for it.…”
Section: Discussionsupporting
confidence: 50%
“…Also, higher V m / V ant ratios were associated with smaller falls in SBP during dialysis, whether calculated using the postdialysis SBP or the lowest measured intradialytic BP. These results are consistent with data from Inrig et al (21,22), who found that the highest survival in patients with the greatest intradialytic fall in BP, whereas patients in whom BP did not fall or in whom BP increased, mortality risk was increased. It is tempting to speculate that the increase in V m /V ant and the lower decrement in intradialytic BP in patients in whom V m /V ant was increased were both related to fluid overload.…”
Section: Discussionsupporting
confidence: 83%
“…We have previously identified intradialytic hypertension to be associated with more than a two-fold increase in hazard of hospitalization and death, as well as with higher 2-year mortality (2)(3)(4). In this study, we identified a novel association between the presence of intradialytic hypertension and significant impairment in markers of in vivo endothelial cell function.…”
Section: Resultsmentioning
confidence: 54%
“…Although it has been recognized for decades, recently our laboratory has identified intradialytic hypertension as an independent predictor of adverse clinical outcomes including nonaccess related hospitalization and mortality (2)(3)(4). Despite its clinical significance, little is known about the pathophysiologic mechanisms underlying intradialytic hypertension.…”
Section: Introductionmentioning
confidence: 99%